Multiobjective H2/H∞ control design with regional pole constraints for damping power system oscillations - Hardiansyah Hardiansyah (Suara Teknik : Jurnal Ilmiah, 2010)
; "> This paper presents multiobjective H2/H∞ control design withregional pole constraints for damping power system oscillations. Thestate feedback gain can be obtained by solving a linear matrixinequality (LMI) feasibility problem that robustly assigns theclosed-loop poles in a prescribed LMI region. The proposedtechnique is illustrated with applications to the design of stabilizerfor a typical single-machine infinite-bus (SMIB) power system. TheLMI-based control ensures adequate damping for widely varyingsystem operating conditions. The simulation results illustrate theeffectiveness and robustness of the proposed stabilizer.Keywords: multiobjective H2 /H ∞ control, regional pole constraints, linear matrixinequality, power system stabilizer, robust control